A dictionary of agricultural and allied terminology - Winburne, John N. (East Lansing : Michigan State University Press, 1962)
The dictionary aims at collecting and defining the words and idioms of agriculture. This became pertinent as the literature of agriculture increases in volume from the vigorous investigation of scholars; as more persons whose native language is not English need to learn the most recent discoveries of agriculture, and as more of urban youths turn to one of the branches of agriculture.
Includes bibliographical references: p. 897-903.
rpm 23/01/2019
Ref
Keywords: Agriculture